Isolation And Identification Of Fungi From Soil And Water In The Bahr Al-Najaf Depression (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the study is to ascertain the biological variety of the fungi living in the Bahr Al-Najaf depression's soil and water. wherethe study session was split into two seasons, with the first season beginning in mid-October and the second in mid-January. With threeduplicates for each location, three water sample collection sites and three soil sample collection sites were chosen. In this study, thewater and soil of Bahr Al-Najaf were used to identify 51 fungal isolates, which were distributed as follows: 34 fungal isolates for thefirst season and 17 fungal isolates for the second season. The fungus isolated during the first season by molecular diagnostics andpolymerase chain reaction technology were two isolates of (A. caespitosus) (C. cladosporioides)3 isolates, (A. niger) 4 isolates, (A.tubingensis) 2 isolates, (A. oryzae)) Two isolates, (A. flavus) 4 isolates, (A. terrus), 4 isolates, (Alternaria arborescens) one isolate,(C. allicinum) one isolate, (Talaromyces helices) one isolate, (C. iridis), one isolate, (Metarhizium anisopliae) one isolate,(Moesziomyces aphidis) one isolate, (F. solani) one isolate, ( Talaromyces funiculosus) one isolate, (Neurospora tetrasperma) oneisolate, (Trichoderma longibrachiatum) one isolate, (A. Irpex) [1] isolate, (A. niveus) [1] isolate.As for the fungal isolates isolated in the second season, they are Fusarium sp (2) isolates, Mucor racemosus (4) isolates, Mucor sp(2) isolates, Paecilomyces sp (3) isolates, A. ibericus (1) isolate, Plectosporium tabacinum (1) isolate, A. fumigatus (1) isolate,Paecilomyces variotii (1) isolate, A. niger (1) isolate, F. culmorum (1) isolate.Five fungal isolates have been recorded globally:(C. allicinum, Moesziomyces aphidis, Talaromyces helices, Neurospora tetrasperma, A. turcosus).